Sierra Leone’s Infrastructure : A Continental Perspective - Pushak, Nataliya (2012)
Infrastructure development in Sierra Leone contributed about half a percentage point to the economy's per capita growth rate in 2003-07. But if Sierra Leone could upgrade its infrastructure to the level of the best performer in Africa, per capita growth rates could be boosted by more than three percentage points. After nine years of peace, economic activity is flourishing at every level in Sierra Leone. But the 11-year civil war destroyed the country's infrastructure, and rebuilding the road network and ports while improving the electrical, water, and telecommunications infrastructure is proving difficult. Looking ahead, expanding electrification is a top priority because current access levels, at only 1-5 percent of the urban population and 0 percent in rural areas, are impeding other development. The water and sanitation sector faces similar challenges, as only 1 percent of the rural population has access to piped water. Sierra Leone has been spending about $134 million annually on infrastructure in recent years. About $66 million is lost each year to inefficiencies. Comparing spending needs against existing spending and potential efficiency gains leaves an annual funding gap of $59 to $278 million per year. If savings from greater efficiency could be fully captured, Sierra Leone would not meet its posited infrastructure targets for another 30 years. Sierra Leone needs to make difficult decisions about the prioritization of infrastructure investments and must think strategically about bundling and sequencing investments for maximum returns.